2011
DOI: 10.1007/978-94-007-2199-9_6
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C Transport and Its Role in the Central Nervous System

Abstract: Vitamin C, or ascorbic acid, is important as an antioxidant and participates in numerous cellular functions. Although it circulates in plasma in micromolar concentrations, it reaches millimolar concentrations in most tissues. These high ascorbate cellular concentrations are thought to be generated and maintained by the SVCT2 (Slc23a2), a specific transporter for ascorbate. The vitamin is also readily recycled from its oxidized forms inside cells. Neurons in the central nervous system (CNS) contain some of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
140
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(143 citation statements)
references
References 105 publications
1
140
0
2
Order By: Relevance
“…In addition to its antioxidant protection, AA participates in numerous cellular functions [33]. Although AA circulates in plasma in micromolar concentrations, it reaches millimolar concentrations in most tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its antioxidant protection, AA participates in numerous cellular functions [33]. Although AA circulates in plasma in micromolar concentrations, it reaches millimolar concentrations in most tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Neurons in the central nervous system (CNS) contain some of the highest AA concentrations of mammalian tissues. Ascorbic acid serves several functions in the CNS, including peptide amidation, myelin formation, synaptic potentiation and protection against glutamate toxicity [33]. NF-jB is a dimeric transcription factor activated by reactive oxygen species [2], and it has been shown that it up-regulates many inflammatory cytokines such as MMP-9 [34].…”
Section: Discussionmentioning
confidence: 99%
“…In the CNS, ascorbate has several functions including antioxidant protection, peptide amidation, myelin formation, synaptic potentiation and protection against glutamate toxicity. 52 Ascorbate has neuroprotective properties against the oxidative damage associated with different neurodegenerative diseases such as Alzheimer's, Parkinson's and Huntington's disease. 52 Thus, the decreased methylation level of CpG site in the SLC23A2 gene in both groups of SMA patients, assuming there is increased expression level of this gene, might denote the SLC23A2 gene could fulfill a certain compensatory function for motor neurons and aid in their survival in SMA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C: Ascorbic acid (vitamin C) is an important antioxidant in intracellular functions, with some of highest concentrations in CNS (202). It easily reacts with reactive oxygen species to neutralize their activity, and become ascorbate free radical, which is then recycled (203).…”
Section: Vitaminsmentioning
confidence: 99%